Effect of Sorbitol Plasticizer on Bioplastics Properties Based on Oil Palm Empty Fruit Bunches (OPEFB) and Jackfruit Seed Starch - Sasria, Nia; Afifah, Vita Nur; Nur Tajalla, Gusti Umindya (Makara Journal of Science, 2025)
In bioplastics, natural materials that are easily decomposed are used to minimize plastic waste. In this research, the compositions used were cellulose from oil palm empty fruit bunches (OPEFB), jackfruit seed starch, and carboxymethyl cellulose (CMC) as a filler with sorbitol as a plasticizer. This study aimed to analyze the effect of a sorbitol plasticizer on bioplastic properties. The study began by extracting jackfruit seed starch and OPEFB cellulose. Subsequently, bioplastics were prepared by varying sorbitol, namely 0 (S – 0), 0.5 mL (S – 0.5), 1 mL (S – 1), and 1.5 ml (S – 1.5), with CMC 20%. As a result, the S – 0 variation showed the highest water resistance at 43.44%. The highest biodegradation test was in the S – 1.5 variation of 48.54% for 6 days in the soil media. The SEM test found voids in the S – 1.5 sample. Next, the best tensile strength test in the S – 0 variation was 5.44 MPa, while the S – 1.5 variation had the optimum elongation value at 13.54%. Overall, the nature of resistance to water and tensile strength were directly proportional. However, these two samples were inversely proportional to biodegradation and elongation. Meanwhile, the characteristics of biodegradation and elongation were directly compared.